Strategi Social Media Marketing Kopi Kamu dalam Membangun Brand awareness Inklusif di Instagram - Muhammad Sadam Wiguna; Oktaviana Purnamasari (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
This article discusses the social media marketing strategy implemented by Kopi Kamu on Instagram to build brand awareness through an inclusive employment identity involving baristas with Down syndrome. The study was developed from a qualitative case study that used interviews, observation, and documentation to examine planning, implementation, integrated communication, and social media integration in the organization. The findings show that Kopi Kamu utilizes Instagram feeds, reels, stories, highlights, consumer interactions, influencer collaboration, and paid boosting to introduce its products and social mission. The inclusive positioning becomes a distinctive brand cue that strengthens recognition, recall, purchase consideration, and consumer consumption experience. However, the strategy still faces limitations related to content consistency, platform diversification, and public misunderstanding regarding disability exploitation. The article argues that inclusive social media marketing can become a meaningful communication strategy when it is supported by transparent storytelling, service quality, local product narratives, and sustained engagement with consumers. The implication is that food and beverage businesses can integrate commercial objectives and social values without reducing the dignity of workers with disabilities.